209 Safety of cycling infrastructure installed during COVID-19 pandemic in Toronto Canada. (20th November 2022) - Rothman, Linda; Namin, Sima; Schwartz, Naomi; Macpherson, Alison; Harris, Anne; Winters, Meghan; Macarthur, Colin; Howard, Andrew
Abstract : Background: In the spring/summer of 2020, 8 new cycling infrastructure corridors (6 downtown) were installed in Toronto, Canada during the COVID-19 pandemic. Changes in cycling volumes and safety (6 cycle tracks and 2 buffered bicycle lanes), pre-versus post-installation were examined. Methods: Cycling volumes were estimated using 34 temporary counters across the city (September 2019 compared to 2020/2021) and 21 downtown permanent bike counters (May 2020 compared to 2021; October 2019 compared with September 2020). Pre- and post- installation cycling volume data on new infrastructure was based on two-day average counts collected in 2020. Police-reported cyclist collisions pre- (2016-Aug 10, 2020, n= 278 collisions) and post-installation (Aug 11, 2020- Dec 31, 2021, n=102 collisions) were mapped within 25-metres of each cycling corridor. Collisions were adjusted by observation time. Results: Cycling volumes increased by 12% across the city [58 to 65 bikes/hour]; 72% downtown (128 to 220 bikes/hour), and 68% on the new infrastructure (106 to 179 bikes/hour). Cycling collision rates decreased 28% on the infrastructure (0.74/1000 to 0.53/1000 cycle months, respectively), with most collisions occurring at intersections with little change post-installation (72% versus 74%, respectively). Conclusion: Cycling volumes increased post installation, most markedly downtown and on the cycling infrastructure. There was a reduction in collisions with the installation of cycling infrastructure; however, the proportion of intersection collisions increased. Learning Outcomes: There was a trend towards increased cycling in Toronto since the beginning of the Covid-19 pandemic. Although collisions declined along new cycling infrastructure, intersections must be designed to improve cycling safety.